2018
DOI: 10.1016/j.neuron.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Signaling Controls Input-Specific Synaptic Plasticity at Striatal Circuits

Abstract: Monoaminergic modulation of cortical and thalamic inputs to the dorsal striatum (DS) is crucial for reward-based learning and action control. While dopamine has been extensively investigated in this context, the synaptic effects of serotonin (5-HT) have been largely unexplored. Here, we investigated how serotonergic signaling affects associative plasticity at glutamatergic synapses on the striatal projection neurons of the direct pathway (dSPNs). Combining chemogenetic and optogenetic approaches reveals that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 84 publications
(124 reference statements)
2
43
0
Order By: Relevance
“…5-HT 4 R were shown to modulate several types of K + -channels 22,63 that leads to a longlasting increase in neuronal excitability, and a previous study in adult rats showed that activation of 5-HT 4 R converted weak synaptic potentiation into persistent LTP in the CA1 area 64 . It has also been shown that 5-HT 4 R activation could prevent the learning-induced facilitation of LTD 65,66 and depotentiation of LTP, in both CA1 and dentate gyrus 67 , while regulating LTD in other brain regions through the modulation of the postsynaptic BK channels 22 . Thus, electrophysiology has suggested that, in addition to the synaptic plasticity effects revealed by the molecular biology exploration, 5-HT 4 activation might also affect cell and/or network excitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT 4 R were shown to modulate several types of K + -channels 22,63 that leads to a longlasting increase in neuronal excitability, and a previous study in adult rats showed that activation of 5-HT 4 R converted weak synaptic potentiation into persistent LTP in the CA1 area 64 . It has also been shown that 5-HT 4 R activation could prevent the learning-induced facilitation of LTD 65,66 and depotentiation of LTP, in both CA1 and dentate gyrus 67 , while regulating LTD in other brain regions through the modulation of the postsynaptic BK channels 22 . Thus, electrophysiology has suggested that, in addition to the synaptic plasticity effects revealed by the molecular biology exploration, 5-HT 4 activation might also affect cell and/or network excitability.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the 5-HT 4 R is coupled to the heterotrimeric G13 protein, which in turn selectively activates the small GTPase RhoA 21 . Recently, post-synaptically expressed 5-HT 4 Rs have been found to gate long-term plasticity of excitatory synapses through a local Ca 2+ -dependent mechanism 22 . This finding has provided initial clues to the long-reported effects of 5-HT 4 R activation on learning, memory, and behavior [23][24][25] , including pathological changes associated with neurodegeneration 26 .…”
mentioning
confidence: 99%
“…Notably, the same presynaptic action of 5‐HT 1B receptor was transient in PFC inputs, indicating that the same receptor controls transient and sustained mechanisms differentially depending on the respective brain regions. In the postsynapse of SPN in the NAc, the 5‐HT 4 receptor inhibits LTD when coupled with repeated stimulation with glutamate and action potentials . In the neocortex, the transient activation of serotonin facilitated LTD in a 5‐HT 2C receptor‐dependent manner …”
Section: Cellular and Synaptic Bases For Sustained Effectsmentioning
confidence: 99%
“…In the postsynapse of SPN in the NAc, the 5-HT 4 receptor inhibits LTD when coupled with repeated stimulation with glutamate and action potentials. 92 In the neocortex, the transient activation of serotonin facilitated LTD in a 5-HT 2C receptor-dependent manner. 93 While behavioral studies have shown that dopamine and serotonin modulate learning and stress responses, whether these neurotransmitters share synaptic and cellular mechanisms has not been well reported.…”
Section: Cellular and Synaptic Bases For Sustained Effectsmentioning
confidence: 99%
“…A micro drill (Cellpoint Scientific Inc.) was used to drill holes through the skull. RV injections were carried out as previously described in adult (12-16-weeks-old) male Shank3B −/− and control Shank3B +/+ littermates (Cavaccini et al, 2018). Injections were performed with a Nanofil syringe mounted on an UltraMicroPump UMP3 with a four channel Micro4 controller (World Precision Instruments), at a speed of 5 nl per seconds, followed by a 5-10 minutes waiting period, to avoid backflow of viral solution and unspecific labelling.…”
Section: Virus Production and Injectionmentioning
confidence: 99%